The Model of Interfaith Pluralism among University Communities in East Nusa Tenggara, Indonesia - Widyawati, Fransiska; Lon, Yohanes Servatius; Midun, Hendrikus; Ungkang, Marcelus (UIN Sunan Gunung Djati Bandung, 2024)
This study examines the dynamics of interfaith relations and religious tolerance among students and lecturers in East Nusa Tenggara (NTT), Indonesia—a pluralistic region known for its strong communal values and peaceful coexistence. The research aims to uncover how everyday interfaith interactions, embedded in local traditions, contribute to maintaining religious harmony amidst global trends of rising extremism and polarisation. Using a quantitative approach, data were collected from 961 respondents across 47 universities through a structured questionnaire. Statistical analyses, including descriptive statistics and one-way ANOVA, were conducted to explore patterns of interfaith engagement, negative experiences, and exclusivist attitudes. Findings indicate a high frequency of positive interreligious interactions and minimal negative experiences such as discrimination or exclusion. Both students and lecturers strongly reject religious exclusivism and violence, with lecturers demonstrating slightly higher tolerance levels. Based on these insights, the study introduces the NTT Interfaith Pluralism Model, which comprises four core principles: interpersonal proximity, cultural anchoring, mutual visibility, and educational responsibility. These principles reflect how religious harmony in NTT is sustained through daily practices, local wisdom, and the role of educators as moral exemplars. The study offers practical implications for fostering inclusive religious environments, especially in multi-faith societies across the Global South. Rather than focusing solely on policy or formal dialogues, this model highlights the power of informal social interaction and community-embedded ethics. The originality of this research lies in its context-sensitive approach and contribution to understanding pluralism in peaceful settings, offering a scalable and replicable framework for other plural societies.